2004
DOI: 10.1038/sj.jp.7211116
|View full text |Cite
|
Sign up to set email alerts
|

Increased Morbidity in Severe Early Intrauterine Growth Restriction

Abstract: Infants born prematurely who are also severely IUGR have higher neonatal morbidity and mortality when compared to infants of similar gestational age. The surviving IUGR infants had less intraventricular hemorrhage and periventricular leukomalacia than less mature infants of comparable birth weight, but a similar incidence of ROP and length of stay. They had a higher incidence of NEC, direct hyperbilirubinemia and chronic lung disease, probably due to end-organ damage in utero from chronic placental insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
3
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(116 citation statements)
references
References 36 publications
4
99
3
10
Order By: Relevance
“…2.1.1 Intra-uterine growth restriction and susceptibility to infection and disease Low-birth-weight piglets in litters with high variation in birth weights experience intra-uterine growth restriction (IUGR), usually resulting in physiological dysfunctions and an increase in neonatal morbidity and mortality (Wootton et al, 1983;Aucott et al, 2004). In addition, IUGR neonates are more susceptible to infection or environmental changes due to an ineffective immune system (Cromi et al, 2009;Zhong et al, 2012), and IUGR animals have abnormal differences in size and histopathology of the thymus (Cromi et al, 2009).…”
Section: Pre-weaning Mortalitymentioning
confidence: 99%
“…2.1.1 Intra-uterine growth restriction and susceptibility to infection and disease Low-birth-weight piglets in litters with high variation in birth weights experience intra-uterine growth restriction (IUGR), usually resulting in physiological dysfunctions and an increase in neonatal morbidity and mortality (Wootton et al, 1983;Aucott et al, 2004). In addition, IUGR neonates are more susceptible to infection or environmental changes due to an ineffective immune system (Cromi et al, 2009;Zhong et al, 2012), and IUGR animals have abnormal differences in size and histopathology of the thymus (Cromi et al, 2009).…”
Section: Pre-weaning Mortalitymentioning
confidence: 99%
“…Intrauterine growth delay appears in second place with 14% of all the stillborn and 6% of all the neonatal deaths 4. Recent studies concerning the influence of intrauterine gro w t h restriction (IUGR) in morbidity and mortality of p re t e rmnewborns have observed that each marker of IUGR was associated with increased mort a l ity and more adverse outcome [5][6][7][8] . A c c o rding to Lubchenco the importance of b i rt h weight and gestational age in the prognosis of n e w b o rnbabies is justified for the important ro l e that both re p resent in the maturation of many systems in preterm infants 9 .…”
mentioning
confidence: 99%
“…Several other studies have researched this question as well and suggest that bleeding risk is not increased in SGA neonates, but most of these studies were also performed in small sample sizes. [13,20,28] The fact that most neonates with major IVH did not have severe thrombocytopenia should not be surprising, since multiple studies have shown that the correlation between thrombocytopenia and bleeding risk is far from clear. [1,6,29,30] Thirdly, we did not record platelet counts after the first 3 days of life, because we focused on early onset thrombocytopenia and prenatal risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that the incidence of thrombocytopenia is 2.7 times higher in SGA neonates compared to a group of AGA neonates matched for gestational age at birth, which is in agreement several other studies. [2,3,7,14,20] The strength of this study, besides being one of the largest studies on early onset thrombocytopenia in SGA neonates, is the study design with a control group matched for gestational age at birth. Matching for gestational age allowed for a more accurate comparison between the two groups (SGA and AGA) by eliminating the important confounding effect of prematurity.…”
Section: Discussionmentioning
confidence: 99%